Problems and Remedies of Teaching of English to Students - Widagdo, Arif (Elementary School Teacher, 2017)
Because of the social and cultural backgroundof the students, a teacher/lecturer of English faces a lot of problems while teaching English to Indonesian students, especially Unnes students (Semarang State University). There are many reasons for this. The first and the most important reason is that Indonesian students have no knowledge of even basic English although they are taught English in Schools. Perhaps the school teachers/lecturers do not pay proper attention towards the teaching of English. Whatever may be the reason for this but the teacher/lecturer who teache s those students in higher classes suffers the most and faces a lot of problems while teaching them a prescribed book or course in higher classes. On the other hand students look towards their teacher/lecturer with great hope. They consider the teacher/lecturer the most competent and think that their teacher/lecturer would make them learn English very soon, thus a teacher/lecturer’s responsibility towards his students is doubled. As a result many English teachers/lecturers are made up and disappointed and so leave the assignment in the middle of their contract. But if the teacher/lecturer has a little patient and is competent and intelligent he would handle the situation easily and achieve his goal. The plans, strategies and methods of teaching English to the students have been discussed in details in the main research paper.